2021
DOI: 10.1177/10482911211023476
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Fishing as an Occupational Determinant of Opioid Overdoses and Deaths of Despair in Two Massachusetts Fishing Ports, 2000–2014

Abstract: The opioid epidemic has had disproportionate effects across various sectors of the population, differentially impacting various occupations. Commercial fishing has among the highest rates of occupational fatalities in the United States. This study used death certificate data from two Massachusetts fishing ports to calculate proportionate mortality ratios of fatal opioid overdose as a cause of death in commercial fishing. Statistically significant proportionate mortality ratios revealed that commercial fisherme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…This same definition has been previously utilized especially in the literature examining "deaths of despair," which have been contributing to increased mortality, of which drug poisonings are the cause of death with the highest number. 7,9,10,35,36 Specific variables obtained from death certificates included cause (s) of death, year of death, usual occupation, usual industry, age, sex, educational attainment, and race/ethnicity. Death certificate occupation and industry data refer to the "usual" occupation and industry of the decedent, meaning the occupation and industry that they tended to work during their life.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This same definition has been previously utilized especially in the literature examining "deaths of despair," which have been contributing to increased mortality, of which drug poisonings are the cause of death with the highest number. 7,9,10,35,36 Specific variables obtained from death certificates included cause (s) of death, year of death, usual occupation, usual industry, age, sex, educational attainment, and race/ethnicity. Death certificate occupation and industry data refer to the "usual" occupation and industry of the decedent, meaning the occupation and industry that they tended to work during their life.…”
Section: Methodsmentioning
confidence: 99%
“…This same definition has been previously utilized especially in the literature examining “deaths of despair,” which have been contributing to increased mortality, of which drug poisonings are the cause of death with the highest number. 7 , 9 , 10 , 35 , 36 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 To isolate the role of occupation in these elevated death rates, Fulmer et al compared commercial fishermen to other workers living in the same Massachusetts fishing ports. 2 They found that opioid poisoning deaths were four times more likely to occur among commercial fishermen than the other workers, even though both groups share many other sociodemographic and cultural characteristics such as housing, education, lifestyle, and traditions.…”
mentioning
confidence: 99%